Online Learning Implementation Training for Teachers of SDN Bangetayu Kulon - Cahyaningtyas, Andarini Permata; Jupriyanto, Jupriyanto; Yustiana, Sari; Kusumadewi, Rida Fironika (Universitas Pendidikan Ganesha, 2021)
The partner in this community service was SDN Bangetayu Kulon, Genuk, Semarang. The teachers experienced difficulties to conduct online learning and assessment. Whatsapp had been their main platform to deliver the material and weekly evaluation to their students. The output targets in this PKM were: (1) creating and operating an online classroom in Edmodo; (2) creating online assessments using Kahoot! and Quizizz; (3) evaluating students learning achievement based on the online assessment. The methods used in this PKM were lecturing, question and answer, and direct practice. The results showed that all teachers have succeeded to create and manage an online class in Edmodo and conducting online assessments by using Kahoot! and Quizizz.